AN EXPERIMENTAL STUDY OF WHISTLE-BLOWING: THE INFLUENCE OF OBEDIENCE PRESSURE AND ETHICAL DILEMMAS - Priska Tandi Gala; Intiyas Utami; Ari Budi Kristanto; Aprina Nugrahesthy Sulistya Hapsari (Asia Pacific Fraud Journal, 2018)
A pressure from other parties and ethical dilemmas can influence accounting staff’s intention to take whistle-blowing action. This study aims to provide empirical evidence about the intention of accounting students to take whistle-blowing action from the perspectives of obedience pressure and ethical dilemmas. Experimental design 2 x 2 between subjects is used by involving 80 participants. The treatment is given in the form of obedience pressure (high and low) and ethical dilemmas (individualist and collectivist).The findings show that the groups with lower obedience pressure and individualist treatment have a higher intention to take whistle-blowing action than the group with higher obedience pressure and collectivist treatment.